Acute Drug Poisoning with QTc Prolongation due to Ingestion of Crushed Dumpling-Form Medications–A Case Report - Onodera, Makoto; Goto, Sayuri; Suzuki, Mitsuko; Ohyama, Asami; Zenda, Rie; Suzuki, Tsuyoshi; Iwabuchi, Masahiro; Iseki, Ken (Archives of Clinical and Medical Case Reports, 2024)
Drug-induced corrected QT interval (QTc) prolongation is a recognized risk factor for torsades de pointes (TdP), a potentially fatal arrhythmia. This report presents a case involving 36-year-old woman with a history of depression and recent overdose attempt. On discovery, the patient was found unconscious, with solid substances adhering to her hands and similar substances present in a cooking bowl. No empty drug packaging was observed at the scene. Acute drug poisoning was suspected, and the patient was transported to our hospital. Electrocardiography revealed a prolonged QTc interval of 483 ms, suggesting drug-induced QT interval prolongation. Urine drug screening was positive for benzodiazepines. The patient later disclosed that she had crushed and ingested her prescribed medications, including escitalopram oxalate, quetiapine fumarate, and famotidine, all of which are associated with QTc prolongation. The respective half-lives were found to be 27–32 hours for escitalopram oxalate, 6–7 hours for quetiapine fumarate, and 2–4 hours for famotidine. Gastric decontamination was initiated, and the QTc interval normalized after more than 32 hours. This case is notable for the unique ingestion method, as prior reports of medication ingestion in dumpling form were not found. This underscores the need for healthcare providers to consider atypical ingestion methods in overdose cases. Additionally, rapid electrocardiographic assessment and close electrocardiogram (ECG) monitoring, with attention to the drug halflife, are essential in preventing potential life-threatening arrhythmias.